Chewing abilities of elderly populations in Europe - Listl, Stefan (International dental journal, 2011)
Purpose: To describe variations in chewing abilities of elderly populations in different European countries. Methods: We used data from the Survey of Health, Ageing, and Retirement in Europe (SHARE Wave 2) and estimated a series of multivariate logistic regression models in order to analyse variations in self-reported ability to bite and chew on hard foods by persons aged 50+ from 14 European countries (P < 0.05). Results: Abilities to bite and chew on hard foods are comparably high in Sweden, Switzerland and the Netherlands but comparably low in Spain, Denmark, France, Greece, Belgium, Italy, Czechia, and Poland. Median levels are observed in Austria, Germany, and Ireland. Conclusions: The best chewing abilities seem to exist amongst elderly populations in Sweden, Switzerland, and the Netherlands but comparably low chewing abilities appear to prevail amongst those in Spain, Denmark, France, Greece, Belgium, Italy, Czechia, and Poland. Future research is encouraged to identify the exact causes and consequences of such disparities in oral health.